(untitled) (Perner’s Contacts, 2012)
This article describes the developed rangefinder measurement device suitable for automatic mapping systems. This device uses a high-quality optical capture sensor and a laser beam. In this article are presented the measurement results and the distance measurement algorithms based on image processing methods. This system is mainly used for distance measurement, but it is suitable for automatic exploration and mapping systems too. The advantage of the developed system is a distance measurement process processing each point on the detected vertical laser beam and the possibility of using low-cost components.